Characteristics of DO, organic matter, and ammonium profile for practical-scale DHS reactor under various organic load and temperature conditions. Issue 7 (3rd April 2018) - Nomoto, Naoki; Ali, Muntjeer; Jayaswal, Komal; Iguchi, Akinori; Hatamoto, Masashi; Okubo, Tsutomu; Takahashi, Masanobu; Kubota, Kengo; Tagawa, Tadashi; Uemura, Shigeki; Yamaguchi, Takashi; Harada, Hideki
ABSTRACT: Profile analysis of the down-flow hanging sponge (DHS) reactor was conducted under various temperature and organic load conditions to understand the organic removal and nitrification process for sewage treatment. Under high organic load conditions (3.21–7.89 kg-COD m −3  day −1 ), dissolved oxygen (DO) on the upper layer of the reactor was affected by organic matter concentration and water temperature, and sometimes reaches around zero. Almost half of the CODCr was removed by the first layer, which could be attributed to the adsorption of organic matter on sponge media. After the first layer, organic removal proceeded along the first-order reaction equation from the second to the fourth layers. The ammoniacal nitrogen removal ratio decreased under high organic matter concentration (above 100 mg L −1 ) and low DO (less than 1 mg L −1 ) condition. Ammoniacal nitrogen removal proceeded via a zero-order reaction equation along the reactor height. In addition, the profile results of DO, CODCr, and NH3 -N were different in the horizontal direction. Thus, it is thought the concentration of these items and microbial activities were not in a uniform state even in the same sponge layer of the DHS reactor.